Cable Bacteria and Their Biotechnological Application - Stiefelmaier, Judith (Advances in biochemical engineering, biotechnology, 2025)
Cable bacteria grow as multicellular filaments several centimetres deep into the sediment of freshwaters and oceans. Hereby, cable bacteria show unique characteristics such as electrogenic sulphur oxidation, extremely high conductivity and ability for CO fixation. This offers several possibilities of future applications in biotechnology with an outlook to sustainable processes. So far, research on cable bacteria is mostly concerning metabolism, electron transfer and effect on the surrounding sediment. Cultures are always performed on sediment from the natural habitat and in simple, small-scale reaction tubes, requiring further development for reproducible cultivation with scale-up capabilities. However, based on the known properties of cable bacteria, possible areas of application can already be derived. The use of cable bacteria in bioremediation is a promising approach, as the degradation of hydrocarbons has already been proven. Co-cultivation with plants could open up a further field of application, such as the described reduction of methane emissions from rice fields. Due to the extremely high conductivity of the filaments, cable bacteria are also very promising for incorporation into biodegradable microelectronics. By integrating electrodes into a suitable reactor system, bioelectrochemical processes could be implemented, either with the goal of electron uptake and product formation or for electricity generation.